Climate Change and Its Emerging Impact on Pediatric Gastrointestinal Infections in Indonesia – A Review Article - Yanni, Daffa Arkananta Putra; Rafiqa Rais Akbar (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2025)
Background: Pediatric gastrointestinal (GI) infections remain a major public health issue in Indonesia, particularly among children under five. These infections are closely linked to poor sanitation, unsafe water, malnutrition, and inadequate healthcare access. Climate change has intensified these challenges, with rising temperatures, floods, and droughts increasingly influencing disease patterns. Despite this growing threat, limited research has explored how environmental changes specifically impact pediatric GI infections in Indonesia. Discussion: Climate change acts as a multiplier of risk for GI infections by disrupting water and sanitation systems, affecting food safety, and limiting hygiene practices. Floods often contaminate drinking water, while extreme heat enhances pathogen survival in food and water. Droughts reduce water availability, limiting handwashing and sanitation. These environmental stressors disproportionately affect vulnerable populations, especially children living in poverty or disaster-prone areas. In addition, climate-related events often disrupt healthcare services and contribute to malnutrition, further increasing children's susceptibility to infections. However, Indonesia’s health and climate policies remain fragmented. There is a lack of integrated research, limited disease surveillance, and insufficient public health preparedness that specifically addresses pediatric needs in a changing climate. Conclusion: To address the growing threat of climate-sensitive pediatric GI infections, Indonesia must strengthen its surveillance systems, invest in climate-resilient health infrastructure, and integrate environmental risks into child health strategies. A coordinated, multisectoral response that prioritizes vulnerable children is essential to reduce disease burden and improve health outcomes in the face of climate change.